The Buddha on Mecca's verandah : encounters, mobilities, and histories along the Malaysian-Thai border - Johnson, Irving Chan (Critical dialogues in Southeast Asian studies., 2012)
The Buddha on Mecca's Verandah examines the many ways in which people living along an international border negotiate their ethnic, cultural, and political identities. This ethnography of a small community of Thai Buddhists in the Malaysian state of Kelantan draws on rich, original vignettes to show how issues such as territoriality, identity, and power frame the experiences of borderland residents. Although the Thai represent less than 10 percent of the Kelantan population, they are vocal about their identity as non-Muslim, non-Malay citizens. They have built some of the world's largest Buddhist statues in their tiny villages, in a state that has traditionally been a seat of Islamic governance. At the same time, the Thai grapple with feelings of social and political powerlessness, being neither Thai citizens nor Muslim Malaysians. This thoughtful study offers new perspectives and challenges the classical definition of boundaries and borders as spaces that enforce separation and distance. With insights applicable to comparative border and frontier studies around the world, The Buddha on Mecca's Verandah will appeal not only to anthropologists but also to specialists in Asian and Southeast Asian studies, cultural geography, religious and ethnic studies, globalization, and cosmopolitanism.